2012
DOI: 10.1186/preaccept-1876233368639637
|View full text |Cite
|
Sign up to set email alerts
|

Existence of the Rdl mutant alleles among the Anopheles malaria vector in Indonesia

Abstract: The existence of the Rdl mutant allele indicates that, either insecticide pressure on the Anopheles population in these areas might still be ongoing (though not directly associated with the malaria control programme) or that the mutant form of the Rdl allele is relatively stable in the absence of insecticide. Nonetheless, the finding suggests that integrated pest management is warranted in malaria-endemic areas where insecticides are widely used for other purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
1
2
0
1
Order By: Relevance
“…; Asih et al . ), and the previous suggestion of recent independent selective sweeps centred on rdl in sympatric populations of An. gambiae and An.…”
Section: Resultssupporting
confidence: 59%
“…; Asih et al . ), and the previous suggestion of recent independent selective sweeps centred on rdl in sympatric populations of An. gambiae and An.…”
Section: Resultssupporting
confidence: 59%
“…For rdl, the 296G mutation was detected in Guinea and Ivory Coast and is the target site for cyclodiene insecticides (e.g., dieldrin), which have been discontinued from use in malaria control programmes. Despite the ban on dieldrin decades ago, molecular analysis studies have shown that despite the A296G substitution declining in some mosquito populations, it has persisted at high frequencies in others [35][36][37][38][39] . Here we show higher allele frequency of A296G mutation in mosquitoes from Ivory Coast when compared with those from Guinea, corroborating a previous report 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to dieldrin has somehow been maintained in natural mosquito populations (Asih et al 2012, Kwiatkowska et al 2013, Wondji et al 2011, although the selective forces causing its persistence remain a puzzle. One possibility is that cyclodienes continue to be used as insecticides in private agriculture, but another is that the Rdl-296 mutations confer crossresistance to other insecticides.…”
Section: Discussionmentioning
confidence: 99%